(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article explains that phraseological units as one of the most important means of creating imagery and emotional-expressiveness are the product of a multifaceted analysis covering cultural, historical, semantic and sociolinguistic aspects among the peoples of Northern Afghanistan, Turkmen and Uzbeks.